Forward-link performance of CDMA cellular system - Ismail, M. S.; Abd. Rahman, Tharek (2000)
The impact of the propagation path-loss exponent on the forward performance of a direct-sequence code-division multiple-access (DS-CDMA) cellular system is investigated. For this purpose, a simple analytical model based on the inverse power-of-distance path-loss exponent law is developed. The problem of finding proper power-control factors is considered. According to path-loss exponent, the proper power-control factors are estimated for optimum performance. With these factors, results show that the capacity is reduced by a half by changing path-loss exponent from 4.5 to 2.5. For this range in path-loss exponent, power control can approximately double the capacity compared to the case of no power control